SEAFLOOR SEDIMENT CHARACTERISTICS AND HEAVY MINERAL OCCURENCES AT BETUMPAK CAPE AND ADJACENT AREA, BANGKA STRAIT, BANGKA BELITUNG PROVINCE - Rohendi Rohendi; Noor C.D. Aryanto (Marine Geological Institute of Indonesia, 2012)
Thirty seafloor of sediment samples have been taken by using gravity corer and grab sampler at Betumpak Cape, and adjacent area of Bangka Belitung. The result of grain size analyses show that there are four sediment units: gravelly sand, gravelly muddy sand, silt and silty sand. Identification of Scanning Electron Microscope (SEM) image on several samples shows the presence of clay mineral such as smectite, alunite, chlorite etc., may resulted from plagioclase weathering of granite. Based on heavy mineral analyses, its highest content is found at MTK-27 (northwest of Betumpak Cape). High content of apatite (0.94% wt and 1.07% wt) is found on coarse sand fractions (115-170 mesh) at MTK-29 (northeast Ular Cape) and MTK-30 (north of Ular Cape). Generally, the heavy mineral accumulation is occurred on medium sand fraction (60-80 mesh) as magnetite (7.86% wt), ilmenite (4.9% wt) and zircon (1.32% wt). Based on these data, it shows that heavy mineral is accumulated on medium to coarse sand. Keywords: sea floor sediment, grain size analysis, heavy minerals, and Betumpak Cape, Bangka strait. Sebanyak 30 sampel sedimen dasar laut telah diambil dengan menggunakan pemercontoh jatuh bebas dan comot di Perairan Tanjung Betumpak dan sekitarnya, Bangka Belitung. Hasil analisis besar butir menunjukkan adanya 4 satuan sedimen, yaitu pasir kerikilan, pasir lumpuran sedikit kerikilan, lanau dan pasir lanauan. Hasil identifikasi citra Scanning Electron Microscope (SEM) terhadap beberapa sampel, memperlihatkan kehadiran mineral lempung seperti smektit, alunit, klorit dll., kemungkinan sebagai hasil pelapukan plagioklas dari granit. Berdasarkan analisis mineral berat kandungan tertinggi terdapat di lokasi MTK-27 (baratlaut Tanjung Betumpak). Akumulasi mineral berat umumnya terdapat pada fraksi pasir ukuran sedang (60-80 mesh) berupa magnetit, ilmenit dan zirkon masing-masing dengan kandungan 7,86 % berat. 4,9% berat dan 1,32% berat. Pada fraksi pasir kasar (115-170 mesh) dijumpai kandungan apatit tertinggi di MTK-29 (timurlaut Tanjung Ular) dan MTK-30 (utara Tg. Ular) sebesar 0,94% berat dan 1,07% berat. Dari data tersebut terlihat, bahwa secara umum mineral berat terakumulasi pada pasir sedang hingga pasir kasar. Kata kunci: Sedimen permukaan dasar laut, analisis besar butir, mineral berat, dan Tanjung Betumpak, Selat Bangka.